Potent oxidation of DNA by Ru(ii) tri(polypyridyl) complexes under visible light irradiation via a singlet oxygen-mediated mechanism. Issue 14 (9th March 2021) - Shao, Jie; Yan, Zhu-Ying; Tang, Miao; Huang, Chun-Hua; Sheng, Zhi-Guo; Chen, Jing; Shao, Bo; Zhu, Ben-Zhan
Abstract : The irradiation of Ru(ii ) tri(polypridyl) complexes with visible light can induce potent oxidation of DNA mediated by 1 O2 via a type II photosensitization mechanism. Abstract : Since Ru(ii ) tri(polypyridyl) complexes can bind DNA in the groove, the chemistry of metallo-groove-binders has been extended to many applications such as artificial photonucleases and DNA recognizers. Here we found that the major product was N -(2-deoxy-β-d - erythro -pentofuranosyl)-spiroiminodihydantoin (dSp) when the nucleoside 2′-deoxyguanosine (dG) was exposed to the visible light irradiation of Ru(ii ) tri(polypyridyl) complexes including Ru(bpy)3 2+ (bpy = 2, 2′-bipyridyl), Ru(OP)3 2+ (OP = 1, 10-phenanthroline) and Ru(DIP)3 2+ (DIP = 4, 7-diphenyl-1, 10-phenanthroline). Interestingly, we found that in the oxidation of dsDNA the major oxidation product is 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodG) instead of dSp. The formation of dSp and 8-oxodG increased significantly in D2 O and decreased markedly with the addition of NaN3 . [ 18 O]-Labeled 8-oxodG was also found to be produced more than non-labeled 8-oxodG under an 18 O2 atmosphere. The above results clearly indicated that 1 O2 was the major oxidant during the oxidation of both dG and dsDNA by the irradiation of Ru(ii ) complexes, which was further confirmed by both ESR spin-trapping and UV methods. Among the above three Ru(ii ) complexes, Ru(DIP)3 2+ is the most efficient photosensitized generator of dG oxidation products, while in the oxidation of dsDNA, Ru(bpy)3 2+ is the most effective. This is the first report that the irradiation of Ru(ii ) polypridyl complexes with visible light can induce potent oxidation of dG and ctDNA to the more mutagenic product dSp and 8-oxodG via an 1 O2 -mediated mechanism. These findings should provide new perspectives for future investigations on whether ubiquitous Ru(ii ) complexes could cause oxidatively generated DNA damage in cellular models.